Mother’s experience in alternate birth positions during second stage of labour - Modi, Sakshi S.; Desai, Dhwani P.; Verma, Ragini N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The main objective of our research was to study mother’s experience in alternate birth positions during second stage of labour. Evidently, providing freedom to choose birthing positions positively impacts the women’s comfort level and intrapartum birthing experience. Methods: In the present study we counselled our antenatal and intranatal patients about the benefits and risks of alternate birthing positions. We enrolled 50 consecutive consenting parturients with prior vaginal delivery, who opted to adopt alternate birth position during second stage of labour. Maternal experience of birthing in alternate positions was compared to her experience in previous childbirth in dorsal position by using a standard pre-validated questionnaire using Likert scale with close ended and open-ended questions. Results: In our study, 49/50 (98%) mothers found alternate positions helpful, 46/50 (92%) mothers reported bearing down was easier, 47/50 (94%) mothers felt they would recommend alternate birth positions to others, for 49/50 (98%) parturients progression of labour was satisfactory, 48/50 (96%) had a good birthing experience, 44/50 (88%) felt duration of labour was less than what they had expected and 46/50 (92%) parturients reported that birthing experience in alternate birth position was more comfortable as compared to their previous delivery. Conclusions: Overall experience of delivering in alternate birth position was positive. Thus, it is clear that when women are informed and educated about their options, they are in a better position to make decisions from the available options and gain a sense of control over their healthcare with improved satisfaction and experience.